Pengaruh Celebrity Endorsment, Citra Merek Dan Word Of Mouth Terhadap Minat Beli Skincare “The Originote” (Studi Kasus Pada Konsumen Generasi Z) - Annisa, Balqis Firdina Nur; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract In this research the author used quantitative research methods in using primary data obtained from respondents' responses to statements in the questionnaire. The results of this research show that celebrity endorsements, word of mouth have a positive and significant effect on interest in buying